Self-assembled 3D-hierarchical structure Cu2ZnSnS4 photocathodes by tuning anion ratios in precursor solution. (3rd February 2016) - Wen, Xin; Luo, Wenjun; Guan, Zhongjie; Shao, Hansen; Fu, Gao; Zhou, Yong; Zou, Zhigang
Abstract: Cu2 ZnSnS4 (CZTS) is one of the most promising light capture materials for solar cells or solar fuels. Construction of 3D hierarchical structure is very important for efficient optoelectronic devices. It is challenging to directly fabricate 3D hierarchical structure CZTS film by a facile solution method. Herein, we present a one-step sol–gel method for fabrication of CZTS thin films with 3D hierarchical structures. For the first time, it is found that the morphologies of thin films can be adjusted between dense, porous and 3D hierarchical structures by tuning anion ratios of Cl − /Ac − in precursor solution. Further analysis suggests the formation of intermediate phases of SnO2 nanoparticles and SnS2 nanosheets by tuning ratios of Cl − /Ac − in precursor solution, which has important effects on the formation of different nanostructures of CZTS. This study can deepen understanding of anion' effect on morphologies of samples using a solution method and forms a reference to prepare novel nanostructures of other materials.